(untitled) (Al-Aasar, 2025)
This study examines the history, functionalities, and effectiveness of traditional and digital diplomacy in today’s global arena. Traditional diplomacy emphasizes formal protocols and physical missions, while digital diplomacy uses digital innovations and social media platforms to expand diplomatic reach and influence. The research methodology uses historical insights and scholarly literature to trace the evolution of diplomacy and identify pivotal moments and transformative shifts. Data collection involved archival research, content analysis, and case studies of significant diplomatic events. The study reveals patterns, parallels, and distinctions between traditional and digital diplomatic practices, providing insights into the transformative influence of technological advancements on diplomatic processes and outcomes. This research offers a nuanced understanding of diplomacy’s adaptation and evolution in response to the digital age.